ANALYSIS OF THE IMPACT OF ABRASIVE TURBID WATERS ON THE INTERNAL PARTS OF PUMPING UNITS DUE TO TURBIDITY OF THE WATER IN THE AMUDARYA RIVER (Academicia Globe: Inderscience Research, 2023)
Rapid wear of water pump parts, dimensional change of parts, expansion of cracks are mainly caused by solid particles contained in the transported water. Their impact on parts (especially on the surface of the body) on parts (especially on the surface of the body) is enhanced in the process of "cavitation", and the impact of abrasive particles on the part increases even more.